1990
DOI: 10.1111/j.1476-5381.1990.tb12965.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thyroid states upon responses of the rat aorta to catecholamines

Abstract: 1 Mechanical responses to various stimulants and the distribution of adrenoceptor subtypes were investigated in smooth muscle cells of the rat aorta in eu-(control), hyper-and hypo-thyroid states. 2 Concentration-response relationships for K showed that the KCI EC50 value was slightly higher (28.4 mm K) in hypothyroid than in euthyroid and hyperthyroid states (22.5 mm and 22.8 mm K, respectively). The order of maximum amplitudes of KCI contraction was control > hypothyroid > hyperthyroid. 3 The EC50 values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
4

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 42 publications
2
14
1
4
Order By: Relevance
“…In addition, this alteration in the responsiveness to vasoconstrictors may play a role in the reduced blood pressure of hypothyroid rats, as well as in the preventive effects of hypothy roidism on experimental hypertension. The results in aortic strips agree with those re ported previously [9,14,16], with the same preparation. However, when the data ob tained in the renal vasculature are compared with the results obtained in other vascular beds, our results confirm the reduced sensitiv ity observed by Brown and Pollock [11] in hindlimb preparations but contrast with the increased responsiveness reported by Koehn et al [7], and with the normal response re ported in the mesenteric vasculature [12,15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, this alteration in the responsiveness to vasoconstrictors may play a role in the reduced blood pressure of hypothyroid rats, as well as in the preventive effects of hypothy roidism on experimental hypertension. The results in aortic strips agree with those re ported previously [9,14,16], with the same preparation. However, when the data ob tained in the renal vasculature are compared with the results obtained in other vascular beds, our results confirm the reduced sensitiv ity observed by Brown and Pollock [11] in hindlimb preparations but contrast with the increased responsiveness reported by Koehn et al [7], and with the normal response re ported in the mesenteric vasculature [12,15].…”
Section: Discussionsupporting
confidence: 82%
“…The data we obtained in aortic strips from hyperthyroid rats agree with those reported by Rahmani et al [14] in aortic strips but con trast with the increased [9] and decreased [13,16] reactivity reported by other authors. In creased reactivity to vasoconstrictors in iso lated perfused kidneys from hyperthyroid rats reported here contrasts with the normal re sponse previously reported in dog hindlimb vasculature [5,6], as well as in the isolated rat mesenteric [12] and hindlimb [7] vascular beds.…”
Section: Discussionsupporting
confidence: 82%
“…Differences in the prepara tion used may be the main cause of discrepan cies, as suggested by our data. In hypothyroid rats, a decreased responsiveness to isoprenaline has also been reported in the mesenteric vascular bed [16] and in the aorta [17], ac cording to the reduced (3-adrenergic receptor concentration observed in the vasculature of these rats [17], The reduced responsiveness to vasodilators in the renal vasculature reported here suggests that this alteration may play a role in the increased total peripheral vascular resistance previously reported in these ani mals [1. 2], It is also interesting to note that the bolus administration of nitroprusside produced a dual response in the preconstricted renal vas culature from hypothyroid rats: vasoconstric tion at low doses and vasodilation at high doses.…”
Section: Discussionmentioning
confidence: 54%
“…7], The influence of hyper thyroidism on p-adrenoceptor-mediated va sodilation appeared to be dependent on the tissue investigated. Both an increased sensi tivity [5,[8][9][10] and unaltered responses [4] towards p-adrenoceptor agonists have been reported for different vascular smooth muscle preparations taken from hyperthyroid ani mals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that some of these symp toms are accompanied by pharmacological al terations. For example, in some but not all tis sues of experimental animals, an upregulation of (i-adrenoceptor density and enhanced ago nist responsiveness have been found [2][3][4][5], The majority of these studies were performed in the heart and large conduit vessels.…”
Section: Introductionmentioning
confidence: 99%